Criminal Liability for Dolus and Negligence of Fiber Optic Cable Operators that Result in Accidents - Deden Ridwan; Moh. Lubsi Tuqo Ramadhan (International Journal of Educational Research & Social Sciences, 2026)
This study examines the criminal liability of fiber optic operators for intentional and negligent acts that harm the public. The main focus is on how positive law and the harmonization of the criminal justice system regulate this responsibility. This research uses a legislative, case, and comparative approach within the framework of normative legal methods. All legal materials (primary, secondary, and tertiary) are analyzed qualitatively to answer the legal issues raised. In addition to providing compensation. The research findings reinforce the existence of negligence by the fiber optic network operator as a corporate entity, whether committed intentionally (dolus) or due to structural negligence (culpa), resulting in legal liability for damage to public facilities in the form of dysfunction of public infrastructure. Business actors sometimes benefit from the crimes they commit, so it is considered unfair to impose criminal sanctions on operators. As the regulator of regional development, local governments also bear responsibility for every policy issued. On the other hand, the restorative justice approach through criminal mediation remains relevant to be integrated into various models of law enforcement. This requires comprehensive harmonization in the criminal justice system—substantively, structurally, and culturally—to be in line with the values ​​of justice in positive law.